The filler effect: The influence of filler content and type on the hydration rate of tricalcium silicate. Issue 7 (10th April 2017) - Kumar, Aditya; Oey, Tandre; Falzone, Gabriel; Huang, Jian; Bauchy, Mathieu; Balonis, Magdalena; Neithalath, Narayanan; Bullard, Jeffrey; Sant, Gaurav
Abstract: The partial replacement of ordinary portland cement (OPC) by fine mineral fillers accelerates the rate of hydration reactions. This acceleration, known as the filler effect, has been attributed to enhanced heterogeneous nucleation of C‐S‐H on the extra surface provided by fillers. This study isolates the cause of the filler effect by examining how the composition and replacement levels of two filler agents influence the hydration of tricalcium silicate (T1‐Ca3 SiO5 ; C3 S), a polymorph of the major phase in ordinary portland cement (OPC). For a unit increase in surface area of the filler, C3 S reaction rates increase far less than expected. This is because the agglomeration of fine filler particles can render up to 65% of their surface area unavailable for C‐S‐H nucleation. By analysis of mixtures with equal surface areas, it is hypothesized that limestone is a superior filler as compared to quartz due to the sorption of its aqueous CO3 2− ions by the C‐S‐H—which in turn releases OH − species to increase the driving force for C‐S‐H growth. This hypothesis is supported by kinetic data of C3 S hydration occurring in the presence of CO3 2− and SO4 2− ions provisioned by readily soluble salts. Contrary to prior investigations, these results suggest that differences in heterogeneous nucleation of the C‐S‐H on filler particle surfaces, caused due to differences in their interfacial properties, have little if any effect on C3 S hydration kinetics.